(untitled) - Wright, Terry (Boca Raton, 2010)
In particular, it presents a consistent notation within and across chapters, updating material when appropriate. Although the authors do account for the astounding growth in the field of computational fluid dynamics that has occurred since publication of the first edition, this text emphasizes traditional "one-dimensional" layout and points the way toward using CFD for turbomachinery design and analysis.
Keywords: Cơ học chất lỏng.,Fluid mechanics.,Máy Tuabin,Turbomachines